2021
DOI: 10.1371/journal.pone.0249336
|View full text |Cite
|
Sign up to set email alerts
|

More popular because you’re older? Relative age effect on popularity among adolescents in class

Abstract: Previous studies have found a significant effect of pupil’s month of birth on their school- and sports performances. The current study investigates whether this so-called relative age effect also exists in a rather unexplored domain, namely popularity among adolescents in school classes. Whereas prior studies examined relative age related to the cut-off date at primary school entry, we also study possible relative age effects regarding the age composition within pupils’ current school class. Data are from nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Our models adjust for a list of potential confounders including: age (van Aalst & van Tubergen, 2021), gender, physical health (Dijkstra et al, 2009), socioeconomic status (Plenty & Mood, 2016), life satisfaction, relationship with parents (Wainright & Patterson, 2008), as well as school-related factors such as friendship satisfaction, classroom relations, and academic evaluation (Freitas et al, 2018; Litwack et al, 2012; Ramos-Vidal, 2016; Wong & Siu, 2017). As a more stringent test of our network brokerage argument, we further include the following sociometric measures that may confound the focal association: indegree, outdegree, network size, and eigenvector (Perry et al, 2018; Wasserman & Faust, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Our models adjust for a list of potential confounders including: age (van Aalst & van Tubergen, 2021), gender, physical health (Dijkstra et al, 2009), socioeconomic status (Plenty & Mood, 2016), life satisfaction, relationship with parents (Wainright & Patterson, 2008), as well as school-related factors such as friendship satisfaction, classroom relations, and academic evaluation (Freitas et al, 2018; Litwack et al, 2012; Ramos-Vidal, 2016; Wong & Siu, 2017). As a more stringent test of our network brokerage argument, we further include the following sociometric measures that may confound the focal association: indegree, outdegree, network size, and eigenvector (Perry et al, 2018; Wasserman & Faust, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…An extreme example is that an athlete born on 1st January is almost 1 year older than an athlete born on 31st December of the same calendar year, though both compete in the same age group. Such age difference during the stage of sports development may provide an advantage to “early-born” athletes who usually outscore their peers in terms of anthropometric and physiological characteristics, which in turn reinforces their psychological characteristics and a mentality of a “winner” ( Drenowatz et al, 2021 ; van Aalst and van Tubergen, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…When the birthplace effect was studied in the Brazilian context, results present some differences. For example, studying athletes competing in Rio de Janeiro Olympic Games 2016, Tozetto et al (2017), showed that most of the Brazilian athletes were from the Southeast and South regions. Further, among those competing in Tokyo Olympic Games 2020, athletes from the Southeast and Northeast regions presented a higher chance of being a medalist (Thuany et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%